CLINICAL EFFICACY OF EYELID MARGIN DEEP CLEANING COMBINED WITH INTENSE PULSED LIGHT IN TREATMENT OF DEMODEX BLEPHARITIS - SU Mei, SU Jingjing, CHENG Dan, LIN Baotao, GUO Ping (精准医学杂志, 2023)
Objective To investigate the clinical efficacy of eyelid margin deep cleaning combined with intense pulsed light (IPL) in the treatment of patients with demodex blepharitis. Methods A total of 60 patients (120 eyes) who were diagnosed with demodex blepharitis in Shenzhen Eye Hospital from July 2021 to March 2022 were enrolled, and according to the treatment modality, they were divided into eyelid margin deep cleaning group (group A with 60 eyes) and eyelid margin deep cleaning+IPL group (group B with 60 eyes). The two groups were compared in terms of Ocular Surface Disease Index (OSDI) score, eyelid inflammation score, meibomian gland opening score, meibomian gland secretion score, meibomian gland loss score, and demodex mite count before treatment and after 2 months of treatment, as well as the changes in these indices after treatment. Results After 2 months of treatment, both groups had significant reductions in OSDI score, eyelid inflammation score, meibomian gland opening score, meibomian gland secretion score, and demodex mite count (t=6.880-15.959,P<0.05), with no significant change in meibomian gland loss score (P>0.05). There were significant differences between the two groups in the changes in OSDI score, eyelid inflammation score, meibomian gland opening score, meibomian gland secretion score, and demodex mite count after treatment (t=2.047-5.685,P<0.05), with no significant difference in the change in meibomian gland loss score (P>0.05). Conclusion Eyelid margin deep cleaning combined with IPL exerts a marked therapeutic effect on demodex blepharitis by alleviating eye discomfort, improving meibomian gland secretion, and reducing the number of demodex mites.